Glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid and preparation method of glycosylated zein / hyaluronic acid composite nanoparticles

The preparation of beta-loaded nanoparticles by antisolvent coprecipitation method of glycosylated zein and hyaluronic acid composite nanoparticles, solving the problems of low preparation efficiency and toxic side effects of carrier materials in the prior art, and achieving high efficiency, Green betastetic acid nanoparticles were prepared, enhancing their water dispersion and anti-tumor activity.

CN119157857APending Publication Date: 2024-12-20INST AGRO PROD PROCESSING ANHUI ACADEMY AGRI SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411306842.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In the prior art, when preparing beta acid-loaded nanoparticles, the method is inefficient and the steps are complicated. The carrier materials used are mostly synthetic polymers or chemical active agents, which have toxic side effects and are not suitable for the food field.

Method used

Glycosylated zein and hyaluronic acid composite nanoparticles were prepared by antisolvent coprecipitation method to improve their water dispersion and sustained release.

Benefits of technology

The preparation of loaded beta-based nanoparticles with high encapsulation rate, uniform particle size distribution, low cost, green and environmentally friendly has been achieved, which significantly enhances the water dispersion and anti-tumor activity of beta-based acid, and is suitable for food and medicine fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119157857A_ABST
    Figure CN119157857A_ABST
Patent Text Reader

Abstract

The invention provides betulinic acid loaded glycosylated zein / hyaluronic acid composite nanoparticles and a preparation method thereof.The preparation method comprises the steps that biomacromolecule glycosylated zein and hyaluronic acid serve as carrier materials, an anti-solvent coprecipitation method is utilized, the zein is dissolved in an ethanol solution, and the betulinic acid loaded glycosylated zein / hyaluronic acid composite nanoparticles are obtained; and dispersing the zein in a water phase system at a certain homogenization rate to reduce the solubility of the zein, and gathering molecules under the action of self-assembly characteristics, thereby gradually forming nano-particles. According to the method disclosed by the invention, hydrogen bonds, electrostatic interaction and hydrophobic interaction are mainly combined, particles are uniformly distributed, the encapsulation efficiency of the betulinic acid is greater than 90%, and the water dispersibility and the slow release characteristic of the betulinic acid are obviously enhanced. The preparation method is simple and easy to operate, low in cost, green and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional composite nanoparticles, and in particular to glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid and a preparation method thereof. Background Art

[0002] Betulinic acid is a lupine-type non-polar pentacyclic triterpenoid compound that exists naturally in a variety of foods and their processing by-products. Betulinic acid is found in the leaves, flowers and fruits of plants such as rosemary, perilla, loquat, clove, birch leaves and bark, coffee leaves and apple peels, and in the peels, pits and flesh of red dates. Betulinic acid has anti-tumor effects both in vivo and in vitro, and is a promising anti-liver cancer drug. However, betulinic acid has poor water solubility and a short half-life in vivo, resulting in low bioavailability, which greatly limits its clinical application. The bioavailability and water solubility of betulinic acid can be improved by nanotechnology, and its anti-tumor effect can be clarified. At present, there is no report on the preparation of nanoparticles loaded with betulinic acid using natural biomacromolecule proteins and polysaccharides. Therefore, the construction of nanocarriers loaded with betulinic acid and the exploration of the anti-tumor activity of betulinic acid in this delivery system provided a new method for improving the water solubility and anti-tumor activity of betulinic acid, and provided new ideas for the development of betulinic acid in the fields of food and medicine.

[0003] Zein is a common safe, green and efficient nano-delivery carrier material in the food industry and has been widely used in the fields of nanoparticles, nanofibers, emulsions and nanocomposite membranes. However, the encapsulation efficiency and stability of single zein nanoparticles are low. After glycosylation modification, the encapsulation efficiency and stability of zein nanoparticles as nano-delivery carriers can be improved.

[0004] Hyaluronic acid is a natural animal polysaccharide that can interact with zein as a delivery carrier for hydrophobic bioactive substances. The composite nanocarrier formed by polysaccharide and modified glycosylated zein can not only improve the water dispersibility of hydrophobic bioactive substances, but also achieve the purpose of sustained release and targeted delivery. Summary of the invention

[0005] Technical problem to be solved: In view of the shortcomings of the prior art, such as low efficiency and complicated steps of the preparation method, the selected carrier materials are mostly artificially synthesized polymers or chemical active agents, which have certain toxic side effects and are not suitable for the food field, the present invention provides a glycosylated zein / hyaluronic acid composite nanoparticle loaded with betulinic acid and a preparation method thereof. The preparation method is simple, and is prepared by anti-solvent co-precipitation method. The prepared composite nanoparticles have uniform particle size distribution, high betulinic acid encapsulation rate, and can improve their water dispersibility, sustained release and anti-tumor activity.

[0006] Technical solution: A method for preparing glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid, comprising the following steps:

[0007] S1: dissolving zein powder in a KCl-NaOH buffer solution with a concentration of 0.2 mol / L and a pH value of 13.0, and magnetically stirring until the zein is completely dissolved to obtain a zein solution, and continuing to add glucose to the zein solution under magnetic stirring, allowing Maillard reaction to occur under heating conditions, and immediately cooling in ice water after reacting for 1-4 hours to stop the reaction, centrifuging the supernatant, and adjusting the pH value of the supernatant to 7.0 with hydrochloric acid;

[0008] S2: dialyzing the supernatant obtained in step S1, and then drying to obtain glycosylated zein powder;

[0009] S3: dissolving hyaluronic acid powder in distilled water, stirring until completely dissolved, and then diluting with anhydrous ethanol to obtain a hyaluronic acid ethanol solution, adding the glycosylated zein powder and betulinic acid powder obtained in step S2 to the hyaluronic acid ethanol solution, continuing to stir until the glycosylated zein and betulinic acid are completely dissolved, and then performing ultrasonic treatment to obtain a dispersion;

[0010] S4: injecting the dispersion obtained in step S3 into distilled water 3 times its volume with a syringe under magnetic stirring, continuing magnetic stirring, and then removing ethanol by rotary evaporation under reduced pressure to obtain glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid from which ethanol has been removed;

[0011] S5: drying the glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid from which the ethanol has been removed obtained in step S4, to obtain powdered glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid from which water has been removed.

[0012] The concentration of zein in the zein solution obtained in step S1 is 1%, the mass ratio of zein powder to glucose is 2:1, the constant temperature heating temperature is 85° C., and the Maillard reaction time is 2 h.

[0013] In the above-mentioned step S2, the molecular cutoff of the dialysis bag is 8000 kDa, the dialysis fluid is distilled water, the dialysis time is 48 hours, and the drying method is freeze-drying for 24 hours.

[0014] In the above-mentioned step S3, the ratio of hyaluronic acid powder to distilled water is (1.666-10) mg / mL; the concentration of ethanol in the hyaluronic acid ethanol solution is 70%, and the mass ratio of hyaluronic acid powder, glycosylated zein powder, and betulinic acid powder is (1-4):20:1; the stirring condition is stirring at 1000 rpm for 60 to 90 min, and the ultrasonic treatment condition is 40 Hz for 20 min.

[0015] In the above-mentioned step S4, the volume ratio of the mixed solution to distilled water is 1:3, the speed of magnetic stirring is 600 rpm, the magnetic stirring time is continued for 30 minutes, and the conditions for reduced pressure rotary evaporation are reduced pressure evaporation at a vacuum degree of 70-100 mbar and a temperature of 40° C. for 15-30 minutes.

[0016] The glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid are prepared by the method for preparing the glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid.

[0017] Beneficial effects: The glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid and the preparation method thereof provided by the present invention have the following beneficial effects:

[0018] 1. The present invention uses betulinic acid with multiple life activities and potential health benefits as a hydrophobic bioactive substance, uses biomacromolecule glycosylated zein and hyaluronic acid as carrier materials, and uses an anti-solvent co-precipitation method to dissolve the zein in an ethanol solution, and then disperses it in an aqueous phase system at a certain homogenization rate to reduce the solubility of the zein, and aggregates between molecules under the action of self-assembly characteristics, thereby gradually forming nanoparticles; the preparation method is simple, easy to operate, low-cost, and green and environmentally friendly.

[0019] 2. The glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid prepared in the present invention are mainly bonded by hydrogen bonds, electrostatic interactions and hydrophobic interactions, and the particles are evenly distributed, the betulinic acid encapsulation rate is greater than 90%, and the water dispersibility and sustained-release properties of betulinic acid are significantly enhanced.

[0020] 3. The glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid prepared by the present invention have no obvious damage to HL7702 cells, can promote the apoptosis of HepG2 cells through the Caspase-3 signaling pathway, and in HepG2 cells, can increase the uptake of BA through the CD44 receptor-mediated endocytosis pathway.

[0021] 4. The glycosylated zein-hyaluronic acid composite nanoparticles loaded with betulinic acid prepared by the present invention provide a new perspective for improving the poor water solubility and low bioavailability of betulinic acid to expand its innovative applications in the fields of functional foods, beverages and medicines. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The effects of different mass ratios of G-zein to HA on the particle size and zeta potential (B) of BA-HANPs. Different lowercase letters (a to e) in the figure represent significant differences (P<0.05).

[0023] Figure 2 XRD (A) and FTIR (B) spectra of BA-HANPs and BA-NPs.

[0024] Figure 3 TEM microscopic images of BA-NPs (A and B) and BA-HANPs (C and D).

[0025] Figure 4 The survival results of free BA, BA-NPs and BA-HANPs in HepG2 cells (A) and HL7702 cells (B) after treatment for 24 hours; scatter plot of HepG2 cells after treatment with BA-NPs and BA-HANPs for 24 hours (C); apoptosis results of HepG2 cells after treatment with BA-NPs and BA-HANPs for 24 hours (D); BA concentration is 10 μg / mL.

[0026] Figure 5 This is the effect of composite nanoparticles on genes in the Caspase-3 pathway of cell apoptosis.

[0027] Figure 6 The effect of composite nanoparticles on the proteins of Caspase-3 signaling pathway of cell apoptosis; (A) is the expression of apoptosis-related proteins; (B) is the statistical analysis result of the expression of apoptosis-related proteins.

[0028] Figure 7 is the fluorescence intensity of FITC-IgG1 and FITC-CD44 in HepG2 cells.

[0029] Figure 8 Uptake of FITC-NPs and FITC-HANPs in HepG2 cells (A) and quantitative analysis of fluorescence intensity (B). DETAILED DESCRIPTION

[0030] In order to make the purpose, content and advantages of the present invention clearer, the present invention is further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. After reading the present invention, modifications to various equivalent forms of the present invention by those skilled in the art all fall within the scope defined by the appended claims of the present application.

[0031] The sources of reagents and instruments used in the following examples are as follows.

[0032] Materials and Reagents:

[0033] Betulinic acid (purity ≥ 98%) was purchased from Nanjing Chunqiu Biotechnology Co., Ltd.; zein (protein content 92%) and dimethyl sulfoxide (DMSO) were purchased from Sigma-Aldrich, USA; hyaluronic acid (HA, molecular weight 1.0×10 5 , purity 99%) was purchased from Xi'an Baichuan Biotechnology Co., Ltd.; CCK-8 kit and Annexin V-FITC apoptosis detection kit were purchased from Beijing Solebow Company; human hepatoma cell HepG2 and human normal liver cell HL 7702 were purchased from the Chinese Academy of Sciences; penicillin and streptomycin were purchased from Harbin Pharmaceutical Group; FBS, DMEM high glucose medium, 1640 medium, and trypsin digestion solution were purchased from Gibco, USA; FITC-labeled mouse anti-human CD44 antibody (FITC-CD44) and FITC-labeled mouse IgG1 isotype control (FITC-lgG1) were purchased from Novus Biologicals, USA.

[0034] instrument:

[0035] Nano-laser particle size analyzer (ZEN3600, Malvern, UK), constant temperature magnetic stirrer (S22-2 model, Shanghai Siler Instrument Co., Ltd.), transmission electron microscope (JEM-1230, Japan Electronics Co., Ltd.), pH meter (PB-10, Sartorius, Germany), rotary evaporator (R-100, Buchi, Switzerland), high-speed centrifuge (GL-10MD, Hunan Xiangyi Co., Ltd.), freeze dryer (FD5-series, Ximeng International Group Jinximeng Instrument Co., Ltd.), water bath constant temperature oscillator (SHA-BA, Honghua Instrument Factory, Jintan, Jiangsu), carbon dioxide incubator and Fluoroskan multifunctional microplate reader (ThermoScientific, USA), high performance liquid chromatograph (Agilent, USA), Fourier transform infrared spectrometer and X-ray diffractometer (Bruker, Germany), inverted fluorescence microscope (DMI4000B, Leica, Germany), flow cytometer (Tecan, Switzerland).

[0036] This embodiment provides a method for preparing glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid, which is prepared by anti-solvent co-precipitation method, and the specific steps are as follows:

[0037] (1) dissolving zein powder in a KCl-NaOH buffer solution with a concentration of 0.2 mol / L and a pH value of 13.0, and magnetically stirring until the zein is completely dissolved to obtain a zein solution with a concentration of 1% zein, and continuously adding glucose to the zein solution under magnetic stirring, wherein the mass ratio of the zein powder to the glucose is 2:1, and allowing Maillard reaction to occur under heating conditions. After reacting for 2 hours, the mixture is immediately cooled in ice water to stop the reaction, and the supernatant is separated by centrifugation, and the pH value of the supernatant is adjusted to 7.0 with hydrochloric acid;

[0038] (2) dialyzing the supernatant obtained in step (1), the molecular cutoff of the dialysis bag being 8000 kDa, the dialysate being distilled water, the dialysis time being 48 h, and then freeze-drying for 24 h to obtain glycosylated zein (G-zein) powder;

[0039] (3) Weighing 50, 100, 150 or 200 mg of hyaluronic acid (HA) powder, respectively, adding 30 mL of distilled water and stirring until completely dissolved, then diluting the volume to 100 mL with anhydrous ethanol to obtain a hyaluronic acid ethanol solution, then adding 1 g of the glycosylated zein powder prepared in step (2) and 50 mg of betulinic acid (BA) powder to the above hyaluronic acid ethanol solution, continuing to stir at 1000 rpm for 60 to 90 min until the glycosylated zein powder and the betulinic acid powder are completely dissolved, and then ultrasonically treating at 40 Hz for 20 min to obtain a dispersion;

[0040] (4) under stirring at 600 rpm, 40 mL of the mixed solution prepared in step (3) was quickly poured into 120 mL of distilled water using a syringe within 2 min, and after magnetic stirring for 30 min, ethanol was removed by rotary evaporation at 45 °C to prepare ethanol-removed betulinic acid-loaded glycosylated zein / hyaluronic acid composite nanoparticles (expressed as BA-HANPs);

[0041] (5) Drying the glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid from which the ethanol has been removed obtained in step (4) to obtain powdered glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid from which water has been removed.

[0042] The above step (3) prepared four dispersions of glycosylated zein / hyaluronic acid composite nanoparticles (BA-HANPs) loaded with betulinic acid with different component ratios, and their G-zein:BA:HA ratios were 100:5:5, 100:5:10, 100:5:15, and 100:5:20, respectively.

[0043] Comparative Example 1

[0044] According to the preparation method of Example 1, a glycosylated zein (G-zein) dispersion and G-zein particles were prepared without adding hyaluronic acid powder and betulinic acid powder.

[0045] Comparative Example 2

[0046] According to the preparation method of Example 1, a dispersion of glycosylated zein (expressed as BA-NPs) loaded with betulinic acid and BA-NPs particles were prepared without adding hyaluronic acid powder, wherein the ratio of G-zein to BA was 100:5.

[0047] The BA-HANPs dispersions, G-zein dispersions, and BA-NPs dispersions prepared in the above examples and comparative examples with a G-zein:BA:HA ratio of 100:5:5, 100:5:10, 100:5:15, and 100:5:20 were partially refrigerated in a refrigerator at 4°C for particle size, potential, and other analyses; and partially freeze-dried for solid-state characterization analysis. The specific process and conclusions are as follows.

[0048] 1. Test methods

[0049] 1.1 Determination of particle size, zeta potential, encapsulation efficiency and loading capacity of composite nanoparticles

[0050] The particle size and zeta potential of the composite nanoparticles were measured using a Malvern Nano-ZS dynamic light scattering particle size analyzer. Before the measurement, the freshly prepared nanoparticle dispersion was diluted a certain multiple and equilibrated in the instrument for 60 seconds to avoid multiple particle effects. All measurements were performed at 25°C, and each sample was measured three times and the average value was taken.

[0051] The ultrafiltration centrifugation method was used to determine the BA encapsulation efficiency (EE%) and loading capacity (LC) in the composite nanoparticles. The specific operation method is as follows.

[0052] Determination of encapsulation efficiency (EE%): The encapsulation efficiency of BA was determined by ultrafiltration centrifugation. 1 mL of freshly prepared BA-HANPs nanoparticles and BA-NPs nanoparticles were added to an ultrafiltration tube with a molecular weight cutoff of 10 kDa. The mixture was centrifuged at 4000 rpm for 30 min. The filtrate that overflowed the filter membrane was taken out, and 1 mL of methanol was added to the ultrafiltration tube for further centrifugal extraction. The above operation was repeated twice and the filtrate was combined. After filtering through a 0.22 μM organic filter membrane, the filtrate was tested by HPLC. HPLC conditions: the chromatographic column was a Waters Symmetry C18 column (5 μm, 250 mm × 4.6 mm), the mobile phase was composed of acetonitrile: water (75:25%, v / v), the flow rate was 1.0 mL / min, the detection wavelength was 210 nm, and the column temperature was maintained at 30 ° C. The encapsulation efficiency of BA-HANPs and BA-NPs was calculated as follows:

[0053]

[0054]

[0055] 1.2 Characterization of composite nanoparticle structure and morphology

[0056] FTIR, XRD and TEM were used to characterize the G-zein-hyaluronic acid nanoparticles loaded with BA. The specific operation method is as follows.

[0057] FTIR analysis: Accurately weigh 1 mg of zein, G-zein, BA powder and completely freeze-dried BA-HANPs and BA-NP nanoparticles, grind and mix them with 50 mg of completely dried potassium bromide powder, press them into thin films with a tablet press and scan them. Use potassium bromide tablets as blank controls to subtract background, and set the scanning spectrum range to 400-4000 cm -1 The software OMNIC8.0 was used to smooth the collected FTIR spectrum curves, automatically correct the baseline and analyze the data.

[0058] TEM observation: Use a pipette to drop a small amount of diluted BA-HANPs and BA-NP nanoparticle suspension onto the copper grid containing the carbon support film. After drying overnight, observe on the TEM at a voltage of 100 kV.

[0059] XRD analysis: The freeze-dried BA-HANPs and BA-NP nanoparticle powders were evenly spread on a sample cell dedicated to X-diffraction, with a diffraction angle of 2θ, a scanning angle range of 10 to 60°, and a scanning speed of 0.02° / s.

[0060] 1.3 In vitro antitumor activity test of composite nanoparticles

[0061] HepG2 human liver tumor cells and HL7702 human normal liver cells were selected as the subjects for the efficacy study of composite nanoparticles. The survival rates of the two cells were detected by CCK-8 method to explore the in vitro antitumor activity of G-zein-hyaluronic acid nanoparticles loaded with BA (Liu et al. 2021). The culture methods of HepG2 cells and the detection methods of CCK-8 kit are as follows.

[0062] HepG2 cell culture and treatment: When resuscitating HepG2 cells, take the cells out of liquid nitrogen, place them in a 37°C water bath and shake them repeatedly to thaw them as quickly as possible, then add fresh culture medium to mix, centrifuge to remove the freezing solution and culture medium, add fresh growth medium again, and re-inoculate them in a culture dish, culture at 37°C, 5% CO2 and saturated humidity, and change the medium every 24 hours. HepG2 cell growth medium consists of 90% DMEM high-glucose medium, 10% fetal bovine blood, and 100U / mL penicillin / streptomycin.

[0063] Cytotoxicity test: To investigate the inhibitory effects of free BA, BA-NPs and BA-HANPs on the proliferation of HepG2 cells, 40 mg of BA powder was first completely dissolved in 1 mL of DMSO and then diluted with growth medium to 40 μg / mL, 20 μg / mL, and 10 μg / mL concentration gradients. In addition, BA-NPs and BA-HANPs nanoparticles were dispersed with growth medium and prepared into solutions with the above concentration gradients (based on BA content). HepG2 cells were seeded in 96-well plates at a seeding density of 1×10 4 / well, after culturing in the incubator for 24 hours, the original culture medium was discarded, and then 100 μL PBS was added to each well to remove the residual culture medium. Then 100 μL of culture medium containing different concentrations of free BA, blank nanoparticles or drug-loaded nanoparticles was added to the wells, and the culture was continued for 24 hours or 48 hours, with at least 6 parallel tests in each group. The inhibitory effect of BA and its nanoparticles on the proliferation of HepG2 cells was analyzed using the CCK-8 kit. Add 10 μL of CCK-8 solution to each well, continue to culture for 2 hours, and measure the absorbance at 450 nm with an enzyme reader. The cell viability calculation formula is as follows:

[0064] Cell survival rate*(%)=[A S -A0] / [A C -A0]×100

[0065] A S : absorbance of wells with cells, CCK-8 solution, and BA nanoparticles;

[0066] A0: absorbance of wells with culture medium and CCK-8 solution but no cells;

[0067] AC : Absorbance of wells with cells, CCK-8 solution but without BA nanoparticles.

[0068] HL7702 cells were cultured according to the method of Chen et al. (Chen et al. 2018). HL7702 cells were cultured in 1640 complete medium containing 10% fetal bovine serum and 1% streptomycin. The incubator conditions were 37°C and 5% CO2. The cells were treated every 8 h. HepG2 and HL7702 cells were seeded in 96-well plates at a seeding density of 5×10 3 / well. After being placed in the cell culture incubator for 24 hours, the original culture medium was discarded, and the culture medium containing free BA, BA-NPs and BA-HANPs was added to continue culturing for 24 hours. The BA concentration of each group was 10, 20, and 40 μg / mL, and a blank control group was set up. The cell survival rate was determined using the CCK-8 kit.

[0069] 1.4 Hepatoma cell uptake assay

[0070] The effect of BA on the uptake of composite nanoparticles in liver cancer cells was investigated. Nanoparticles were prepared according to the method of the present invention, and BA was replaced by FITC to obtain BA-NPs and BA-HANPs nanoparticles with fluorescent properties (Gausterer et al. 2021), which were denoted as FITC-NPs and FITC-HANPs, respectively. HepG2 cells in the logarithmic growth phase were taken and incubated at 1×10 5 Cells were inoculated on a 6-well plate at a density of 100 cells / well. After culturing for 24 hours, the original culture medium was discarded, and 3 mL of culture medium containing 20 μg / mL FITC-NPs and FITC-HANPs was added to the wells for further incubation for 2 hours. The culture medium was then aspirated and rinsed with cold PBS solution for 3 times. The HepG2 cells were then placed under an inverted fluorescence microscope for observation. Another 3 mL of 20 μg / mL FITC-NPs and FITC-HANPs culture medium was taken and further diluted to 10 μg / mL and 5 μg / mL. The culture medium of each concentration was added to each well and incubated for 2 hours. After washing with PBS 3 times, the cells were digested with trypsin and centrifuged at 1000 rpm for 5 minutes. The cell pellet was ultrasonically dissolved with 4 mL of methanol solution and centrifuged again to obtain the supernatant. The fluorescence intensity of the supernatant was measured by a fluorescence spectrophotometer. The excitation wavelength was 494 nm and the emission wavelength was 518 nm.

[0071] 1.5 CD44 receptor expression test on tumor cell surface

[0072] The CD44 receptor expression test of composite nanoparticles in HepG2 cells was performed according to the method of Wang et al. (Wang et al. 2012). FITC-CD44 antibody was selected to label CD44 in HepG2 cells, and FITC-IgG1 was used as a control to analyze its fluorescence signal in flow cytometry to explore the effect of BA-loaded G-zein-hyaluronic acid nanoparticles on the expression of CD44 receptor on the surface of HepG2 cells. First, HepG2 cells were cultured at 1×10 5 The cells / well density was inoculated in a 6-well plate. After culturing for 24 hours, the culture medium was discarded, and then 3 mL of culture medium containing BA-HANPs (final BA equivalent concentration was 20 μg / mL) was added. After 4 hours, the cells were trypsinized, and finally resuspended with PBS containing 5% fetal bovine serum and incubated on ice in the dark for 10 minutes, and rinsed once with PBS. 20 μL 0.5 mg / mL FITC-CD44 antibody was added to the HepG2 cells treated with BA-HANPs, and 20 μL 0.5 mg / mL FITC-IgG1 was added as a control group, and continued to incubate on ice in the dark for 30 minutes. The incubated HepG2 cells were resuspended with PBS and placed in a flow cytometer to detect the fluorescence intensity.

[0073] 1.6 Cell apoptosis detection assay

[0074] The experimental method for detecting cell apoptosis by flow cytometry is as follows.

[0075] HepG2 cell suspension was inoculated in a 6-well plate at a density of 1×10 6 / well. The 6-well plate was placed in an incubator and cultured for 24 hours. After the cells adhered to the wall, the culture medium was removed and culture medium containing BA-NPs and BA-HANPs nanoparticles (BA concentration was 20μg / mL) was added respectively. After continuing to culture for 24 hours, the culture medium was discarded, digested with 0.5mL of trypsin, and the cells were collected by centrifugation at 1000rpm. Annexin V-FITC conjugate (195μL) and Annexin V-FITC (5μL) were added to the centrifuge tube, and then 10μLPI was added and shaken. After reacting at room temperature in the dark for 15 minutes, it was detected by flow cytometry. The results were analyzed using FlowJo software.

[0076] The treatment groups were BA-NPs and BA-HANPs.

[0077] 1.7 Real-time fluorescence quantitative PCR and Western blot

[0078] The expression levels of Caspase-3, Bax, Bcl-2 and other Caspase-3 pathway genes and proteins in HepG2 cells were detected as follows.

[0079] Extraction of total RNA from HepG2 cells and real-time fluorescence quantitative PCR: HepG2 cells were inoculated in 12-well plates at a density of 1.0×105 / mL. When the cell density reached 80%, G-zein dispersion, BA-NPs and BA-HANPs nanoparticles (BA concentration of 30μg / mL) were added to continue culturing the cells for 48h. After incubation, the cells were washed with PBS and total RNA in the cells was extracted using Trizol reagent. The collected cells were lysed into a uniform solution, and then 200μL of chloroform was added and mixed. After standing at room temperature for 2min, the solution was centrifuged at 12000rpm for 10min. The supernatant was mixed with an equal volume of isopropanol, incubated on ice for 15min, centrifuged at 12000rpm for 15min, the supernatant was discarded, 1mL75% ethanol was added to wash the precipitate, centrifuged at 7500rpm at 4℃ for 5min, the supernatant was discarded, and the solution was dried at room temperature for 10min. Finally, 40μL of DEPC water was added to dissolve the RNA and placed in a -80℃ refrigerator for use. The RNA concentration was determined using NanoDrop2000, and RNA samples with OD 260 / 280 values ​​between 1.9 and 2.1 were used for subsequent experiments. The synthesis of the first strand of cDNA was based on the instructions of the RT Reagent Kit with gDNA Eraser reverse transcription kit, and real-time fluorescence quantitative PCR was performed according to the instructions of the TB Green II kit, with β-actin (actinbeta, β-actin) as the internal reference gene. The primer sequences were based on Table 1 below, and the reaction procedure was as follows: (1) pre-denaturation at 95°C for 30s; (2) 95°C for 5s to 60°C for 30s, with 40 cycles; (3) adding a melting curve.

[0080] Table 1

[0081]

[0082] Extraction of intracellular protein: (1) Aspirate the culture medium, rinse the cells 3 times with pre-cooled PBS buffer, and add 200uL RIPA lysis buffer (containing protease inhibitors). (2) Shake gently to mix, scrape the cells with a cell scraper, collect them in a 1.5mL centrifuge tube, vortex for 30 seconds, lyse on ice for 30 minutes, centrifuge at 4°C, 13000rpm for 10 minutes, collect the supernatant, which is the total cell protein. (3) Use the BCA kit to determine the concentration of each protein sample. (4) Add 5× protein loading buffer to ensure that the final protein concentration of each sample is consistent, boil in boiling water for 10 minutes to fully denature the protein, and store at -80°C for later use after aliquoting.

[0083] Western blot protein expression detection: (1) Absorb 20 μg of total protein for SDS-PAGE electrophoresis. (2) Use a semi-dry transfer device to transfer the target protein band to a PVDF membrane soaked in methanol. After blocking with 5% skim milk powder for 2 hours, incubate the primary antibody overnight at 4°C on a shaker. (3) After washing the membrane 3 times with TBST (15 minutes each time), incubate the secondary antibody for 1 hour on a shaker at room temperature. (4) After washing the membrane 3 times with TBST (10 minutes each time), prepare ECL luminescent solution and use a chemiluminescent imager to detect the target protein band. β-actin was used as an internal reference for relative protein abundance.

[0084] The treatment groups were G-zein, BA-NPs and BA-HANPs. After 48 h of treatment, the cells were collected and total RNA and protein were extracted.

[0085] 1.8 Data Analysis Methods

[0086] SPSS19.0 was used to analyze the data, and the results were expressed as mean ± standard deviation. At least three biological replicates were set for each treatment group. One-way ANOVA was used to compare the significance of the results, and Turkey's method was used for multiple comparisons. Different letters indicate significant differences between groups (*P<0.05, **P<0.01).

[0087] 2. Results and Discussion

[0088] 2.1 Particle size, zeta potential, encapsulation efficiency and loading capacity of composite nanoparticles

[0089] When preparing composite nanoparticles, it was found that the ethanol-water dispersion systems of HA, BA and BA-HA all showed a clear and transparent appearance, while the appearance of BA-NPs and BA-HANPs nanoparticles was a uniform colloidal dispersion. The average particle size and zeta potential of each sample, such as Figure 1As shown. Compared with the average particle size of G-zein particles of 123.5nm, the average particle size of BA-NPs nanoparticles loaded with BA is reduced to 89.4nm. Zein is rich in proline, and small molecules such as phenols are more likely to combine with it to form a tighter composite structure, which may be the reason why the particle size of nanoparticles becomes smaller after loading small molecule compounds (Patel et al. 2010). The charge properties of composite nanoparticles are mainly determined by the charge characteristics of the outer biopolymer, and when the particle size is small, the greater the absolute value of the zeta-potential, the better the physical stability of the colloidal particles (Yu et al. 2016). As shown in 1, the negative charge on the surface of G-zein in the water-ethanol dispersion system is -20.5mV. After loading BA, the charge on the surface of BA-NPs nanoparticles is -22.6mV. This is mainly because the positively charged region contained in the small molecule polypeptide chain in the G-zein structure is easier to combine with the negatively charged region of BA, making BA-NPs have higher stability (Mehdizadehetal. 2021).

[0090] After adding HA, the average particle size of BA-HANPs nanoparticles increased significantly to 367.4nm (P<0.05). As the amount of HA added continued to increase, the average particle size of BA-HANPs nanoparticles first decreased and then increased. When the addition ratio of G-zein to HA in the system was 100:15 (w / w), the average particle size of the nanoparticles was the minimum of 213.4nm. With the increase of HA addition, the zeta potential of BA-HANPs nanoparticles became smaller and smaller. When the addition ratio of G-zein to HA in the system was 100:20 (w / w), the zeta potential of the nanoparticles reached a minimum of -39.5mV. These results indicate that HA interacts with G-zein and effectively attaches to the surface of BA-NPs nanoparticles. With the increase of HA addition, more HA interacts with G-zein by electrostatic repulsion, which reduces the particle size and surface charge of BA-HANPs nanoparticles, prevents the aggregation of BA-HANPs nanoparticles, and forms a more stable composite particle structure (Zhang et al. 2020). When the mass ratio of G-zein to HA in the system exceeds 100:15, the particle size of the nanoparticles increases slightly. This may be because the attachment of HA to the surface of G-zein has been saturated, resulting in excessive cross-linking of excessive HA and G-zein (Chen et al. 2018). Xie et al. also reported similar results that increasing the shellac content in zein-shellac composite nanoparticles can lead to an increase in particle size through intermolecular cross-linking (Xie et al. 2019).

[0091] The effect of the addition ratio of G-zein to HA on the encapsulation efficiency and drug loading of BA-HANPs is shown in Table 2. After adding HA, the encapsulation efficiency of BA-HANPs was significantly higher than that of BA-NPs at the same ratio (P<0.05). As the mass ratio of G-zein to HA gradually increased from 100:5 to 100:20, the encapsulation efficiency and loading capacity of BA-HANPs increased, reaching a maximum of 93.22% and 3.83%, respectively. This may be because the longer molecular chain of HA increases the surface area of ​​the nanoparticles, and the increase in HA content provides more space for interaction with G-zein, thereby increasing the encapsulation rate and loading capacity of BA (Zhu et al. 2022). The new chitosan derivative has a long-chain molecular structure, so it can encapsulate more curcumin and thus improve its encapsulation efficiency (Zhu et al. 2021). Based on the above analysis results of the particle size, zeta-potential, encapsulation efficiency (EE) and loading capacity (LC) of the composite colloidal particles, in order to obtain stable BA-HANPs with high encapsulation efficiency and high loading capacity, BA-HANPs prepared under the conditions of G-zein:BA:HA of 100:5:20 were selected for subsequent experiments.

[0092] Table 2

[0093]

[0094]

[0095] Note: Different lowercase letters (ad) in each column represent significant differences (P<0.05), longitudinal comparison.

[0096] 2.2 Characterization of composite nanoparticle structure and morphology

[0097] Figure 2 The results of X-ray diffraction and near-infrared spectroscopy of BA-HANPs and BA-NPs are shown in Figure 2. Figure 2 As shown in (A), the main characteristic peaks of unencapsulated BA appear at 13.61°, 14.28°, and 19.11°, indicating that BA has a crystalline structure and a high degree of crystallinity. The X-ray diffraction pattern of zein has two broad slow peaks at diffraction angles 2θ of 11.2° and 13.5°, indicating that zein is an amorphous structure (He et al. 2015). After BA was encapsulated in particles, the XRD diffraction patterns of BA-HANPs and BA-NPs did not show the characteristic crystalline peaks of BA, proving that BA was successfully encapsulated in the particles in an amorphous state. Figure 2Middle (B) shows that the characteristic peaks of BA are located at 541.99 cm-1 (O=CO stretching vibration), 792.74 cm-1 (CC stretching vibration) and 885.33 cm-1 (CC stretching vibration), which is consistent with the results reported by Saneja et al. (Saneja et al. 2017). After BA interacts with protein / polysaccharide, the absorption peaks of the amide I band and amide II band of the nanoparticles shift. This result can be explained by the fact that HA covers and convolutes on the corn protein nanoparticles through electrostatic attraction, while BA is embedded in the protein nanoparticles through hydrophobic interaction (Jacinto et al. 2022).

[0098] The morphology of BA-HANPs and BA-NPs nanoparticles was observed by transmission electron microscopy. Figure 3 It can be seen that both BA-HANPs and BA-NPs nanoparticles are monodispersed uniform spherical particles. The introduction of HA did not cause significant changes in the morphology of the nanoparticles.

[0099] 2.3 In vitro antitumor activity test of composite nanoparticles

[0100] The effects of free BA, BA-NPs and BA-HANPs on the viability of HepG2 and HL7702 cells were investigated. Figure 4 It can be seen that as the BA concentration increased from 10μg / mL to 40μg / mL, the inhibitory effects of free BA, BA-NPs and BA-HANPs on HepG2 cell proliferation increased from 21.18%, 18.19% and 34.38% to 59.79%, 57.55% and 64.37%, respectively. Compared with free BA, BA-NPs showed weaker ability to inhibit cell proliferation of HepG2 cells at all concentrations, while BA-HANPs had a slightly stronger inhibitory effect on HepG2 cell proliferation. At the same concentration, the inhibitory effect of BA-NPs on HepG2 cell proliferation was significantly lower than that of BA-HANPs (P<0.05). This shows that HA-modified BA-HANPs has an enhanced inhibitory effect on liver cancer cells and can improve the anti-tumor activity of BA in BA-HANPs (Wu et al. 2022). Figure 4 It can be seen that free BA, BA-NPs and BA-HANPs had no obvious damage to human normal liver cells HL7702 at all concentrations, indicating that BA is a safe and effective potential anti-tumor drug. Folic acid-modified sorafenib-loaded bovine serum albumin nanoparticles can target liver cancer cells and enhance the anti-tumor activity of sorafenib (Gao et al. 2019).

[0101] Annexin V-FITC / PI double staining technique was used to analyze the effect of BA-HANPs on HepG2 cell apoptosis. Figure 4 It can be seen that the proportion of early apoptosis and late apoptosis of HepG2 cells after BA-HANPs treatment reached 27.1%, which was significantly higher than the proportion of early apoptosis and late apoptosis of HepG2 cells after BA-NPs treatment of 22.2% (P<0.05), which is consistent with the previous CCK-8 test results. Yu Yang prepared BA nanoliposomes pH-BA-LP with pH targeting properties. Its half-inhibitory concentrations for five types of colon cancer cells SW620, HCT116, HT29, SW1116 and CT26 and normal colon cells HCoEpiC were 56.11, 43.23, 59.49, 56.63, 66.35 and 89.11 μM, respectively, indicating that pH-BA-LP is selective for colon cancer cells, and the inhibitory effect of pH-BA-LP on each cell is stronger than that of free BA (Yu Yang 2020). In summary, BA-HANPs can target HepG2 cells and induce cell apoptosis, significantly enhancing the anti-tumor activity of BA.

[0102] 2.4 Effects of composite nanoparticles on the expression of apoptosis-related proteins in HepG2 cells

[0103] The apoptosis process of HepG2 cells is regulated by various apoptotic factors, including CytC, Bcl-2 and Bax in the Bcl-2 protein family, Caspase-3 and Caspase-9 in the Caspase family, etc. BA may promote the apoptosis process of liver cancer cells by regulating the above factors. Figure 5 and Figure 6 The expression levels of Caspase-3, Bax and Bcl-2 genes and proteins in HepG2 cells after treatment with G-zein, BA-NPs and BA-HANPs, respectively. As shown in the figure, the expression level of Bcl-2 in the BA-NPs and BA-HANPs groups was significantly lower than that in the G-zein group (P<0.05), and the expression levels of Bax, Bax / Bcl-2 and Caspase-3 were significantly higher than those in the G-zein group (P<0.05), indicating that BA-NPs and BA-HANPs composite nanoparticles can inhibit the proliferation of liver cancer cells by activating the Caspase-3 signaling pathway. In addition, compared with the BA-NPs group, the expression level of Bcl-2 in HepG2 cells treated with the BA-HANPs group was significantly reduced (P<0.05), and the expression levels of Bax and Caspase-3 were significantly increased (P<0.05), indicating that the BA nanoparticles modified with HA have a stronger activation effect on tumor cell apoptosis-related proteins.

[0104] BA can effectively regulate the expression of various apoptosis-related proteins, thereby inhibiting the proliferation of liver cancer cells. Low expression of Bcl-2 can promote mitochondrial rupture in HepG2 cells, activate various apoptotic proteins and regulate intracellular calcium concentration; high expression of Bax can enhance its effects of inducing mitochondrial permeability changes, activating apoptotic proteins, and releasing cytochromes; high expression of Caspase-3 can destroy HepG2 extracellular matrix proteins, skeleton proteins and cleave DNA repair-related molecules, which helps to promote the apoptosis of HepG2 cells (Wang et al. 2021). HA-modified BA liposomes can be used for targeted treatment of liver cancer. Studies have found that BA, BA-l and HA-BA-L have no inhibitory effect on the activity of normal hepatocytes, but have a dose- and time-dependent effect on the proliferation of HepG2 cells (Ghosh et al. 2021). Western blot results showed that HA-modified BA liposomes can regulate the expression of Bcl-2 and Bax in HepG2 cells, indicating that HA-modified BA liposomes are an excellent CD44-mediated intracellular delivery system with a targeted effect. HA can effectively activate the Caspase-3 pathway, thereby initiating the apoptosis process of liver cancer cells (Wu et al. 2022).

[0105] 2.5 Effect of composite nanoparticles on the expression of CD44 receptor on the surface of HepG2 cells

[0106] CD44 is a transmembrane glycoprotein widely distributed on the cell surface, which is mainly involved in the adhesion of tumor cells to host cells or matrix. Taking advantage of the fact that CD44 can be specifically expressed on the surface of HepG2 cells, the receptor substance corresponding to CD44 is modified on the surface of the nano-delivery carrier, thereby achieving the targeting effect of drug-loaded nanomaterials on HepG2 cells (Lin Shijie et al. 2019). Studies have found that mesoporous silica nanoparticles can recognize CD44 on the cell membrane of MCSs after being modified with HA, thereby enhancing the uptake of particles (Huang et al. 2013). This study took advantage of the specific antigen-antibody interaction between CD44 and HA in HepG2 cells. When BA-HANPs act on HepG2 cells, CD44 can be used as a target, so that BA can be targeted to HepG2 cells. Figure 7 The results show the expression of CD44 receptor on the surface of HepG2 cells. The fluorescence intensity of the FTIC-CD44 antibody staining group of HepG2 cells was significantly higher than that of the isotype control, indicating that HepG2 cells highly express CD44 receptors, which can increase the uptake of BA-HANPs nanoparticles by HepG2 cells through the CD44-mediated endocytosis pathway.

[0107] 2.6 Uptake of composite nanoparticles by HepG2 cells

[0108] FITC is a common fluorescent dye, commonly used in fluorescent antibody technology, which can bind to various antibody proteins and has strong green fluorescence in alkaline solutions (Li et al. 2022). FITC is not only chemically stable, but also has similar solubility to BA. In this study, FITC was selected as a fluorescent dye to replace BA to explore the uptake of BA-loaded G-zein-hyaluronic acid nanoparticles in HepG2 cells. Figure 8 (A) is a fluorescence microscopy image of HepG2 cells treated with FITC-NPs and FITC-HANPs. As shown in the figure, the fluorescence intensity of HepG2 cells treated with FITC-HANPs was significantly higher than that of the FITC-NPs group. Figure 8 (B) is the quantitative analysis result of fluorescence intensity of HepG2 cells after treatment with FITC-NPs and FITC-HANPs. Compared with the FITC-NPs-treated group, the fluorescence intensity of cells treated with FITC-HANPs at concentrations of 20 μg / mL, 10 μg / mL and 5 μg / mL increased by 2.71, 3.57 and 6.24 times, respectively.

[0109] 2.7 Conclusion

[0110] (1) The present invention successfully prepared betulinic acid-loaded glycosylated zein / hyaluronic acid composite nanoparticles BA-HANPs, wherein the optimal mass ratio of G-zein:BA:HA is 100:5:20, i.e., 20:1:4.

[0111] (2) BA-NPs and BA-HANPs particles are uniformly spherical, BA is embedded in an amorphous state, and the stability of the composite nanoparticles mainly depends on hydrophobic effects, electrostatic interactions and hydrogen bonds.

[0112] (3) BA-NPs and BA-HANPs had no obvious damage to HL7702 cells, but could effectively inhibit the proliferation of HepG2 cells and promote their apoptosis. The inhibitory effect of BA-HANPs on the proliferation of HepG2 cells was stronger than that of BA-NPs. Both BA-NPs and BA-HANPs could inhibit the expression level of Bcl-2 in HepG2 cells, promote the expression levels of Bax and Caspase-3, and promote the apoptosis of HepG2 cells through the Caspase-3 signaling pathway. The activation effect of BA-HANPs on the Caspase-3 signaling pathway was significantly stronger than that of BA-NPs.

[0113] (4) In HepG2 cells, FITC-labeled BA nanoparticles can increase the uptake of BA through the CD44 receptor-mediated endocytosis pathway.

[0114] The above embodiments describe the implementation methods of the present invention in detail, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the field without departing from the purpose of the present invention. The above description is only a preferred feasible embodiment of the present invention, and does not limit the scope of rights of the present invention. All equivalent structural changes made by using the contents of the present invention specification are included in the scope of rights of the present invention.

Claims

1. A method for preparing glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid, characterized in that The following steps are involved: S1: dissolving zein powder in a KCl-NaOH buffer solution with a concentration of 0.2 mol / L and a pH value of 13.0, and magnetically stirring until the zein is completely dissolved to obtain a zein solution. Glucose is continuously added to the zein solution under magnetic stirring, and Maillard reaction occurs under heating conditions. After reacting for 1-4 hours, the solution is immediately cooled in ice water to stop the reaction, and the supernatant is separated by centrifugation, and the pH value of the supernatant is adjusted to 7.0 with hydrochloric acid; S2: dialyzing the supernatant obtained in step S1, and then drying to obtain glycosylated zein powder; S3: dissolving hyaluronic acid powder in distilled water, stirring until completely dissolved, and then diluting with anhydrous ethanol to obtain a hyaluronic acid ethanol solution, adding the glycosylated zein powder and betulinic acid powder obtained in step S2 to the hyaluronic acid ethanol solution, continuing to stir until the glycosylated zein and betulinic acid are completely dissolved, and then performing ultrasonic treatment to obtain a dispersion; S4: injecting the dispersion obtained in step S3 into distilled water 3 times its volume with a syringe under magnetic stirring, continuing magnetic stirring, and then removing ethanol by rotary evaporation under reduced pressure to obtain glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid from which ethanol has been removed; S5: drying the glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid from which the ethanol has been removed obtained in step S4, to obtain powdered glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid from which water has been removed.

2. The method for preparing a betulinic acid-loaded glycosylated zein / hyaluronic acid composite nanoparticle according to claim 1, characterized in that: The concentration of zein in the zein solution obtained in step S1 is 1%, the mass ratio of zein powder to glucose is 2:1, the constant temperature heating temperature is 85° C., and the Maillard reaction time is 2 h.

3. The method for preparing a betulinic acid-loaded glycosylated zein / hyaluronic acid composite nanoparticle according to claim 1, characterized in that: In step S2, the molecular cutoff of the dialysis bag is 8000 kDa, the dialysis fluid is distilled water, the dialysis time is 48 h, and the drying method is freeze-drying for 24 h.

4. The method for preparing a betulinic acid-loaded glycosylated zein / hyaluronic acid composite nanoparticle according to claim 1, characterized in that: In step S3, the ratio of hyaluronic acid powder to distilled water is (1.666-10) mg / mL; the concentration of ethanol in the hyaluronic acid ethanol solution is 70%, and the mass ratio of hyaluronic acid powder, glycosylated zein powder, and betulinic acid powder is (1-4):20:1; the stirring condition is stirring at 1000 rpm for 60 to 90 min, and the ultrasonic treatment condition is 40 Hz for 20 min.

5. The method for preparing the glycosylated zein / hyaluronic acid composite nanoparticles loaded with betulinic acid according to claim 1, characterized in that: In step S4, the volume ratio of the mixed solution to distilled water is 1:3, the speed of magnetic stirring is 600 rpm, the magnetic stirring time is continued for 30 minutes, and the conditions for reduced pressure rotary evaporation are reduced pressure evaporation at a vacuum degree of 70-100 mbar and a temperature of 40° C. for 15-30 minutes.

6. Betulinic acid-loaded glycosylated zein / hyaluronic acid composite nanoparticles prepared by the method for preparing betulinic acid-loaded glycosylated zein / hyaluronic acid composite nanoparticles according to any one of claims 1 to 5.